Analisa Pengendalian Persediaan dalam Hubungannya Dengan Efisiensi Biaya pada Kandatel Ambon - Tahapary, Grace (Universitas Brawijaya, Indonesia, 2016)
Abstract: This study aims to see inventory control related to cost efficiency in Kandatel Ambon. Thus, Kandatel Ambon serve as theresearch object and data source in order to support this study. The data analysis uses to analyze inventory control related to cost efficiency, therefor it uses forecasting analyzer, Economic order quantity, reorder point and reorder cycle. The result shows that by using economic order quantity, there will be cost savings Rp. 555 534 556 by booking back 3 times. The lead of Kandatel Ambon needs to use a calculation method economically and not depend on instinct or forecasting. Therefore, the availability of droop wire does not accumulate or otherwise reduce in the warehouse.